Effect of dietary organic selenium and zinc on the internal egg quality of quail eggs for different periods and under different temperatures - Fernandez, IB [UNESP] (2011)
The objective of this study was to evaluate the internal quality of eggs of Japanese quails fed diets supplemented with chelated selenium and zinc. The experiment was carried out for 120 days, and 144 birds were divided in random blocks into four treatments (control; 0.3 ppm Se; 60 ppm Zn and 0.3 ppm Se + 60 ppm Zn). Ten, 14, 18, and 22 weeks after the beginning of lay, eggs were collected and stored under two different temperatures (environmental temperature or refrigeration) and for 10, 20, and 30 days. Eggs were analyzed for: Haugh units (HU), albumen height (AH), yolk index (YI), and albumen index (AI). Parameters were only statistically influenced by the interaction between dietary treatment and storage time. It was concluded that the addition of organic Se and Zn influenced internal egg quality when eggs were stored up to 20 days, independently of storage temperature, suggesting that the combined supplementation of organic Se and Zn improve internal egg quality and extend egg shelf life.